ENGLISH PHONICS LEARNING USING ONLINE GAME AMONG MALAYSIAN PRIMARY SCHOOL STUDENTS: THE UPSHOTS AND THEIR PERCEPTIONS - Baharudin, Nur Afiqah Amalina; Md Yunus, Melor (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Due to the lack of phonemic awareness in English, it is hard for students to read in this language appropriately. As reading competence is very important to be highlighted, this issue need to be scrutinized in order to ensure that students could acquire the phonics learning thus, developing their reading skill. So, this study attempts to investigate the implementation of online game in learning English phonics and their perceptions about the lesson among Year 1 students in SK Kopok, Pasir Gudang, Johor. To acquire this, a set of questionnaires was distributed to all participants involved and all of them have been interviewed in order to gather the data in depth. Pre and post tests were utilized to determine if there any significant difference occurs throughout this study. These instruments were administered among the Year 1 students in this school and there were 15 participants involved in the study. The analysis of the data reveals that most of the students have improved their English phonics lessons by using online game. It is highly significant to determine the reasons that contribute to the findings as this would help various stakeholders to enhance the reading ability among the students. The theory of Jean Piaget regarding the assimilation and accommodation will be drawn deeply in this study as it provides the understanding of how learning takes place when playing the online game. This paper will also discuss the recommendations to improve the phonics lesson as to attract the students’ attention as well as to motivate them to read in English. Thus, the results in the findings will be further discussed throughout this paper.